Character Education Management Strategy Based on Local Wisdom from the Maqashid Syariah Perspective in State High School - Ria Sukandi; Muammar Muammar; Adi Fadli (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Character education in the era of globalization faces challenges of moral decadence and the decline of social ethics. This study aims to deeply examine the management strategy of character education based on local wisdom from the perspective of Maqashid Shariah in State Senior High Schools (SMAN), particularly in the Bayan region, North Lombok. The research method employed is qualitative with a literature review (library research) approach, utilizing descriptive-analytical methods. The results indicate that the integration of Bayan local wisdom values such as mutual cooperation (gotong royong), tolerance, religiosity, and respect for nature with the five principles of Maqashid Shariah (hifẓ al-dīn, hifẓ al-nafs, hifẓ al-‘aql, hifẓ al-nasl, and hifẓ al-māl) can be operationalized through Thomas Lickona's framework encompassing modeling, practice, and reflection. This study successfully formulates the Character Education Management Strategy Model Based on Local Wisdom from the Maqashid Shariah Perspective (MSK- MQ), which is built upon three main pillars: the philosophical pillar (Maqashid Shariah), the cultural pillar (Bayan Local Wisdom), and the managerial pillar (School- Based Management). This strategy is holistically implemented through the curriculum, school culture, extracurricular activities, and teacher modeling. Character education in the era of globalization faces challenges of moral decadence and the decline of social ethics. This study aims to deeply examine the management strategy of character education based on local wisdom from the perspective of Maqashid Shariah in State Senior High Schools (SMAN), particularly in the Bayan region, North Lombok. The research method employed is qualitative with a literature review (library research) approach, utilizing descriptive-analytical methods. The results indicate that the integration of Bayan local wisdom values such as mutual cooperation (gotong royong), tolerance, religiosity, and respect for nature with the five principles of Maqashid Shariah (hifẓ al-dīn, hifẓ al-nafs, hifẓ al-‘aql, hifẓ al-nasl, and hifẓ al-māl) can be operationalized through Thomas Lickona's framework encompassing modeling, practice, and reflection. This study successfully formulates the Character Education Management Strategy Model Based on Local Wisdom from the Maqashid Shariah Perspective (MSK- MQ), which is built upon three main pillars: the philosophical pillar (Maqashid Shariah), the cultural pillar (Bayan Local Wisdom), and the managerial pillar (School- Based Management). This strategy is holistically implemented through the curriculum, school culture, extracurricular activities, and teacher modeling.